Three-dimensional dust mapping of 12 supernovae remnants in the Galactic anticentre - Yu, Bin; Chen, B Q; Jiang, B W; Zijlstra, A (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT We present three-dimensional (3D) dust mapping of 12 supernova remnants (SNRs) in the Galactic anticentre (Galactic longitude l between 150○ and 210○) based on a recent 3D interstellar extinction map. The dust distribution of the regions, which cover the full extents in the radio continuum for the individual SNRs, is discussed. Four SNRs show significant spatial coincidences between molecular clouds (MCs) revealed from the 3D extinction mapping and the corresponding radio features. The results confirm the interactions between these SNRs and their surrounding MCs. Based on these correlations, we provide new distance estimates of the four SNRs, G189.1+3.0 (IC443, $d=1729^{+116}_{-94} \rm \, pc$), G190.9–2.2 ($d=1036^{+17}_{-81} \rm \, pc$), G205.5+0.5 ($d=941^{+96}_{-94}$ or $1257^{+92}_{-101} \rm \, pc$), and G213.0–0.6 ($d=1146^{+79}_{-80} \rm \, pc$). In addition, we find indirect evidences of potential interactions between SNRs and MCs for three other SNRs. New distance constraints are also given for these three SNRs.